The Amber spyglass - Pullman, Philip 1946- (London Scholastic UK Ltd, 2000)
Lyra and Will find themselves at the center of a battle between the forces of the Authority and those gathered by Lyra's father, Lord Asriel.
AIT-4265g, donated by Ivan Anthony S. Henares, AIT, UP.
Keywords: Belacqua, Lyra (Fictitious character) -- Juvenile fiction; Parry, Will (Fictitious character) -- Juvenile fiction; Fantasy fiction